Lead‐Free, Air‐Stable All‐Inorganic Cesium Bismuth Halide Perovskite Nanocrystals. (30th August 2017) - Yang, Bin; Chen, Junsheng; Hong, Feng; Mao, Xin; Zheng, Kaibo; Yang, Songqiu; Li, Yajuan; Pullerits, Tõnu; Deng, Weiqiao; Han, Keli
Abstract: Lead‐based perovskite nanocrystals (NCs) have outstanding optical properties and cheap synthesis conferring them a tremendous potential in the field of optoelectronic devices. However, two critical problems are still unresolved and hindering their commercial applications: one is the fact of being lead‐based and the other is the poor stability. Lead‐free all‐inorganic perovskite Cs3 Bi2 X9 (X=Cl, Br, I) NCs are synthesized with emission wavelength ranging from 400 to 560 nm synthesized by a facile room temperature reaction. The ligand‐free Cs3 Bi2 Br9 NCs exhibit blue emission with photoluminescence quantum efficiency (PLQE) about 0.2 %. The PLQE can be increased to 4.5 % when extra surfactant (oleic acid) is added during the synthesis processes. This improvement stems from passivation of the fast trapping process (2–20 ps). Notably, the trap states can also be passivated under humid conditions, and the NCs exhibited high stability towards air exposure exceeding 30 days. Abstract : Bleifrei und komplett anorganisch sind Cs3 Bi2 X9 ‐Perowskit‐Nanokristalle (NCs; X=Cl, Br, I). Die ligandumhülllten Cs3 Bi2 Br9 ‐NCs geben eine blaue Photolumineszenz mit einem Quantenwirkungsgrad bis 4.5 % ab und sind über einen Monat lang stabil.